Between (Racial) Groups and a Hard Place: An Exploration of Social Science Approaches to Race and Genetics, 2000–2014. (1st September 2016) - Byrd, W. Carson; Best, Latrica E.
ABSTRACT: As the social sciences expand their involvement in genetic and genomic research, more information is needed to understand how theoretical concepts are applied to genetic data found in social surveys. Given the layers of complexity of studying race in relation to genetics and genomics, it is important to identify the varying approaches used to discuss and operationalize race and identity by social scientists. The present study explores how social scientists have used race, ethnicity, and ancestry in studies published in four social science journals from 2000 to 2014. We identify not only how race, ethnicity, and ancestry are classified and conceptualized in this growing area of research, but also how these concepts are incorporated into the methodology and presentation of results, all of which structure the discussion of race, identity, and inequality. This research indicates the slippage between concepts, classifications, and their use by social scientists in their genetics-related research. The current study can assist social scientists with clarifying their use and interpretations of race and ethnicity with the incorporation of genetic data, while limiting possible misinterpretations of the complexities of the connection between genetics and the social world.